2005
DOI: 10.1590/s0103-90162005000500008
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-related changes in respiration and Q10 coefficient of Guava

Abstract: Guava (Psidium guajava L.) is a tropical fruit that presents fast post-harvest ripening; therefore it is a very perishable product. Inappropriate storage temperature and retail practices can accelerate fruit quality loss. The objective of this study was to evaluate the respiratory activity (RA), the ethylene production (EP) and Q 10 of guava fruit at different storage temperatures. 'Paluma' guava fruits were harvested at maturity stage 1 (dark-green skin) and stored at either 1, 11, 21, 31 or 41ºC; RA and EP w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
13

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 15 publications
1
22
0
13
Order By: Relevance
“…The inhibition of loss of green colour in guava held in low oxygen and elevated carbon dioxide can be primarily due to the effects of modified atmosphere on slowing down the metabolic activities leading to retarded ethylene sensitivity and biosynthesis, lower ripening changes and delayed senescence. (Beaudry 1993;Bron et al 2005;Jacomino et al 2001a).…”
Section: Equilibrium Timementioning
confidence: 99%
See 3 more Smart Citations
“…The inhibition of loss of green colour in guava held in low oxygen and elevated carbon dioxide can be primarily due to the effects of modified atmosphere on slowing down the metabolic activities leading to retarded ethylene sensitivity and biosynthesis, lower ripening changes and delayed senescence. (Beaudry 1993;Bron et al 2005;Jacomino et al 2001a).…”
Section: Equilibrium Timementioning
confidence: 99%
“…It was observed that guava is a climacteric fruits that ripens rapidly, highly perishable, and shelf-life period's ranges from 2 to 3 days at room temperatures at 25°C and 1 week at 20°C (Bassetto et al 2005;Jacomino et al 2001b;Bron et al 2005;Chitarra et al 2002). Reyes and Paull (1995) observed that mature green guavas attained full yellow colour in 11 days of storage at 12 and 15°C.…”
Section: Equilibrium Timementioning
confidence: 99%
See 2 more Smart Citations
“…Abaixo desta temperatura os frutos não amadurecem satisfatoriamente, caracterizando o dano pelo frio. No entanto, estas temperaturas permitem um curto período de armazenamento, pois não ocorre uma grande redução no metabolismo dos frutos, havendo necessidade de se associar a outras técnicas pós-colheita (BRON et al, 2005).…”
Section: Introductionunclassified